Curriculum Management During the Covid-19 Emergency - Arini, Putri Dwi; Matin, Matin; Zulaikha, Siti (LPPM Undiksha, 2021)
The spread of the Covid-19 outbreak that hit the world has resulted in many countries closing teaching and learning activities both in schools and other educational institutions. The management of the curriculum which was running during the Covid-19 emergency is very interesting to examine, especially there is still little research that discusses curriculum management during special conditions. This research is expected to provide information on how emergency curriculum management works against the global pandemic. This study aims to analyze distance learning activities through curriculum management for the Covid-19 emergency period. The research method used a descriptive qualitative approach and the research subjects were the principal, teachers, and several students who were taken based on the appointment. Data collection techniques through observation, interviews and documentation. The findings from the study show that the curriculum management system during the Covid-19 emergency has been running as it should, curriculum planning involving local officials and school authorities, organizing by disseminating curriculum programs to all teachers, implementing online learning is constrained due to school conditions and limited technology owned by students and this is a factor that makes online learning not effectively implemented, and curriculum evaluation is based on input from the school and does not involve students and parents of students.